Ronchamp, South Wall - Providência, Paulo (2022)
The Ronchamp Chapel was conceived under the sign of the metamorphoses of memory, appearing as a particular case of memorabilia. Among the memory objects produced by L-C, a plaster model of the first version of the south wall remains as a fragment. Produced through sculpture molding techniques, the perforated surface opens up new possibilities of interpretation of the chapel's analogical design process. The design method of Ronchamp moves between emotional, unconscious images, in search of an architectural experience in response to the “archaisms surviving in man.” The experience of an architectural journey is no longer the promenade architecturale, determined by visual compositions, but the anthropological experience of contact with surfaces, the recognition of the object by the circumscription, the crossing of the threshold, the spatial compression, the illumination of the concave surface of the apse, and of the dazzling by the backlight, expanding the unconscious archaic.